Analiza antropologiczna szczątków kostnych pochodzących z grobu skrzynkowego kultury pomorskiej ze stanowiska nr 1 w Kręcieszkach, gm. Bedlno, pow. Kutno, woj. łódzkie - Borowska-Strugińska, Beata; Rychter, Mariusz (Acta Universitatis Lodziensis. Folia Archaeologica, 2019)
During the rescue research carried out in 1987, a box grave of Pomeranian culture dating back to the Hallstatt D. Found in it, in addition to numerous attachments and lids 36 large vessels, including 23 typical, referred to as urns. Bone remains were preserved only in 21 vessels. Anthropological analysis has shown that human bones come from 21 people, that is, 11 children (under 6 years), 2 children in infans II age (6–14 years), 7 adults (3 men, 3 women and one adult). Only in four cases, lesions were observed.